Predictors of licensure examination for teachers’ performance - Balinario, Jick C.; Ofqueria, Mary Grace M.; Arca, Lina B. (International Research Journal of Science, Technology, Education, and Management)
The study employed a descriptive correlational research design, in which the graduates' academic performance and other factors that significantly predicted their LET performance were examined from the Academic Year 2016-2018. Respondents were randomly selected from a list of NONESCOST LET takers requested from the Professional Regulatory Commission, with a total of 175 respondents identified in this study. The data were analyzed using percentages, means, standard deviations, t-tests, Pearson r, and linear regression analysis. The results revealed that LET takers have difficulty passing the specialization areas in the Licensure examination for teachers. BSEd graduates perform better in the three areas of the exam than non-BSEd graduates. High scholastic ratings and passing admission scores have a better performance in the Licensure examination. Likewise, there was a significant difference between the age, mothers’ educational attainment, course, GPA, and admission entrance score, and no significant difference in civil status, father's educational attainment, and type of school to the LET performance of respondents. There is a significant indirect relationship between the profile of the respondents such as age, course, Entrance Exam, and Grade point average. Lastly, the respondent’s mother's educational attainment, course, GPA, and entrance examination are significant predictors of LET performance. It is recommended the college will concentrate on the area of specialization in the conduct of review classes and strengthen the college-wide admission and retention policy. Non-education graduates who wish to take education units should be given priority to be admitted to the college's postundergraduate program and given enough seminars and review classes.